Preferential Binding of Mg2+ Over Ca2+ to CIB2 Triggers an Allosteric Switch Impaired in Usher Syndrome Type 1J - Vallone, Rosario; Dal Cortivo, Giuditta; D'Onofrio, Mariapina; Dell'Orco, Daniele (Frontiers in Molecular Neuroscience, 2018)
Calcium and integrin binding protein 2 (CIB2) shares with the other members of the CIB family the ability to bind Ca2+ and Mg2+ via two functional EF-hand motifs, namely EF3 and EF4. As a cation sensor, CIB2 is able to switch to a conformation likely associated with specific biological functions yet to be clarified. Recent findings demonstrate the involvement of CIB2 in hearing physiology and a single, conservative point mutation (p.E64D) has been related to Usher Syndrome type 1J (USH1J) and non-syndromic hearing loss. We present an exhaustive biochemical and biophysical characterization of human wild type (WT) and E64D CIB2. We found that CIB2 does not possibly work as a calcium sensor under physiological conditions, its affinity for Ca2+ (Kdapp=0.5 mM) being too low for detecting normal intracellular levels. Instead, CIB2 displays a significantly high affinity for Mg2+ (Kdapp=290 M), and it is probably Mg2+-bound under physiological conditions. At odds with the homologous protein CIB1, CIB2 forms a non-covalent dimer under conditions that mimic the physiological ones, and as such it interacts with its physiological target 7B integrin. NMR spectroscopy revealed a long-range allosteric communication between the residue E64, located at the N-terminal domain, and the metal cation binding site EF3, located at the C-terminal domain. The conservative E64D mutation breaks up such inter-domain communication resulting in the impaired ability of CIB2 to switch to its Mg2+-bound form. The ability to bind the target integrin peptide was substantially conserved for E64D CIB2, thus suggesting that the molecular defect associated with USH1J resides in its inability to sense Mg2+ and adopt the required conformation.